An exploratory study of ecolabelling as an emerging concept in furniture manufacturing - Magbanua, Chelsea Julienne S.
The purpose of this study was to explore ecolabelling as an emerging concept in furniture manufacturing. Data collection was done through personal interviews with the Green Choice Philippines Program Director and ten 10 furniture manufacturers with showrooms in Metro Manila. Grounded theory methods of coding and thematic data analysis were applied in order to establish and analyze common and recurring ideas across the different data gathered. According to the findings of the study, though ecolabelling as a concept in furniture manufacturing was perceived as a beneficial option for the furniture industry to have, there was no sign of the industry prioritizing the development of ecolabels for furniture. As indicated in the data, there were factors that affect the industrys perception on the concept. The study discovered four main reasons that would induce companies to apply for an ecolabel, namely: 1 legal requirement, 2 demand, 3 marketing tool, and (4) concern for the environment. It was also gathered that there were three main hindrances to the development of ecolabels for furniture as perceived by furniture manufacturers. These hindrances were: (1) lack of awareness on ecolabels and environmental sustainability, 2 lack of consumer demand, and (3) cost. In addition, the following factors were revealed regarding Green Choice Philippines that affect the utilization of ecolabels: (1) programs lack of support, manpower and funding from the government, (2) deficiency in information dissemination, and 3 prioritization of green public procurement. In conclusion, in order for the concept of ecolabelling to be perceived as advantageous and vital to the furniture industry, the factors that emerged from the data should first be addressed.